Third Annual Fresno County Young Lawyers Hopper Luncheon with Justice Allen Broussard - Watkins, Howard::::::::: (1984)
Justice Donald Franson shaking hands with Associate Justice Allen Broussard Luncheon at Golden State Plaza ballroom